2017
DOI: 10.1007/s00464-016-5324-9
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of initial endoscopic transluminal drainage are superior to percutaneous drainage for patients with infected pancreatic necrosis: a prospective cohort study

Abstract: The outcomes of initial endoscopic transluminal drainage are superior to percutaneous drainage for patients with infected pancreatic necrosis (ChiCTR-ONRC-13003653).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Other authors have noted that the relatively large variations in reported complication rates in these studies may be partially attributable to the different definitions of complications or in the length of follow-up 17 . The definition of WON resolution, which not only differed between studies but also in terms of the timeframe in which resolution was assessed, ranged from ≤ 4 weeks 28 in some studies to > 1 year in others 34 . In addition, WON size reporting was not standardized, with some studies reporting the length of the longest axis of the WON, and other studies not specifying the dimension being reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have noted that the relatively large variations in reported complication rates in these studies may be partially attributable to the different definitions of complications or in the length of follow-up 17 . The definition of WON resolution, which not only differed between studies but also in terms of the timeframe in which resolution was assessed, ranged from ≤ 4 weeks 28 in some studies to > 1 year in others 34 . In addition, WON size reporting was not standardized, with some studies reporting the length of the longest axis of the WON, and other studies not specifying the dimension being reported.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the title and abstract of the remaining 53 studies, only 14 full-text studies were evaluated for further assessment, and five records were excluded due to incomplete data. Eventually, 9 clinical studies were consistent with the inclusion requirements (17)(18)(19)(20)(21)(22)(23)(24)(25). A detailed study flow-diagram is shown in Fig.…”
Section: Included Trial Characteristics and Quality Assessmentmentioning
confidence: 80%
“…Five included studies (17)(18)(19)(20)24) provided data on endocrine insufficiency, which included 82 cases in the endoscopic approach group and 87 cases in the MIS group. Twelve out of 82 (15.85%) patients who underwent the endoscopic procedure were diagnosed with new-onset diabetes, whereas 27 out of 87 (31.03%) patients who underwent the MIS procedure were diagnosed.…”
Section: Long-term Outcomes: New-onset Diabetes Exocrine Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study, the series included a high proportion of tertiary referrals (85.1%), which was also higher than other high-volume specialist centers [1]. Since the extremely high referral rate, the interval between onset of disease and initial surgical treatment was longer than other centers [1,10,17,18]. Percutaneous or endoscopic drainage was the first step in surgical step-up approach, and many patients were transferred to our hospital after failure of drainage.…”
Section: Discussionmentioning
confidence: 99%